An energy‐efficient MAC protocol based on receiver initiation and multi‐priority backoff for wireless sensor networks - Qi Huamei (Wiley, 2021)
Abstract Wireless Sensor Network (WSN) has been widely used with its main characteristics of resilience, scalability, and mobility. However, the node battery capacity in WSN is limited. In addition, in scenes with emergencies such as forest ecological monitoring, data packets of wildfire emergencies have higher real‐time requirements than periodic normal data. Therefore, this paper proposes an energy‐efficient MAC protocol based on Receiver initiation and Multi‐Priority Backoff (RMP‐MAC). RMP‐MAC adopts the wake‐up matching mechanism initiated by the receiver. The sender adjusts its schedule according to the wake‐up information of the receiver to match the receiver, which reduces the energy consumption of idle listening. In addition, RMP‐MAC proposes a multi‐priority factor adaptive backoff mechanism based on event priority, node remaining energy level, and the number of data packets waiting in the transmission queue, ensuring the transmission of emergency data in the actual situation of forest ecological monitoring. Simulation experiments show that compared with PB‐MAC, AP‐MAC, and MPQ‐MAC, RMP‐MAC can reduce energy consumption by 20.22%, 12.47%, and 6.62% respectively. In addition, it has improved in the average collisions, network throughput, and average delay of packets.